Longitudinally extensive transverse myelitis with anti-myelin oligodendrocyte glycoprotein antibodies following SARS-CoV-2 infection - Dias da Costa, Mariana; Leal Rato, Miguel; Cruz, Diana; Valadas, Anabela; Antunes, Ana Patrícia; Albuquerque, Luísa (Journal of neuroimmunology, 2021)
We report the case of a patient with symptoms of myelopathy following acute SARS-CoV-2 infection. MRI documented a longitudinally extensive transverse myelitis and further investigation was unremarkable with the exception of positivity for MOG-IgG in serum. This report extends the spectrum of post-COVID-19 neurological syndromes, and documents a very significant improvement to long-term oral corticosteroid therapy in this setting. Further prospective studies are needed to establish the risk of recurrence in this subset of patients. [Display omitted] •SARS-CoV-2 associated neuroimmune syndromes are rare but highly debilitating.•Post/para infectious myelitis is typically a longitudinally extensive transverse myelitis.•MOG-IgG positivity in low titers is of unknown significance.•Due to uncertain prognosis, long-term immunosuppression may be warranted.